Increased Apoptosis in the Paraventricular Nucleus Mediated by AT1R/Ras/ERK1/2 Signaling Results in Sympathetic Hyperactivity and Renovascular Hypertension in Rats after Kidney Injury - Zhu, Hongguo; Tan, Lishan; Li, Yumin; Li, Jiawen; Qiu, Minzi; Li, Lanying; Zhang, Mengbi; Liang, Min; Li, Aiqing (Frontiers in Physiology, 2017)
Background: The central nervous system plays a vital role in the development of hypertension, but the molecular regulatory mechanisms are not fully understood. This study aimed to explore signaling in the paraventricular nucleus (PVN) which might contribute to renal hypertension. Methods: Renal hypertension model was established by five-sixth nephrectomy operation (5/6Nx) in male Sprague Dawley rats. Ten weeks afterwards, they were random assigned to no treatment, or intracerebroventricular injection (ICV) with artificial cerebrospinal fluid, losartan (Angiotensin II receptor type 1 (AT1R) antagonist), farnesylthiosalicylic acid (Ras inhibitor), PD98059 (MEK inhibitor), or SB203580 (p38 inhibitor) and Z-DEVD-FMK (caspase-3 inhibitor). Before and after treatment, physiological and biochemical indices were measured. Immunohistochemistry, western blot and RT-PCR were applied to quantify key components of renin-angiotensin system, apoptosis-related proteins, Ras-GTP and MAPKs in the PVN samples. TUNEL assay was used to measure the situ apoptosis in PVN. Results: The 5/6Nx rats showed significantly elevated systolic blood pressure, urinary protein excretion, serum creatinine, and plasma norepinephrine (p<0.05) compared to sham rats. The expression of angiotensinogen, Ang II, AT1R, p-ERK1/2, or apoptosis-promoting protein Bax were 1.08-, 2.10-, 0.74-, 0.82-, 0.83-fold higher in the PVN of 5/6Nx rats, than that of sham rats, as indicated by immunohistochemistry. Western blot confirmed the increased levels of AT1R, p-ERK1/2 and Bax; meanwhile, Ras-GTP and p-p38 were also found higher in the PVN of 5/6Nx rats, as well as the apoptosis marker cleaved caspase-3 and TUNEL staining. In 5/6Nx rats, ICV infusion of AT1R antagonist, Ras inhibitor, MEK inhibitor or caspase-3 inhibitor could lower systolic blood pressure (20.8%-, 20.8%-, 18.9%-, 14.3%-fold) together with plasma norepinephrine (53.9%-, 57.8%-, 63.3%-, 52.3%-fold). Western blot revealed that blocking the signaling of AT1R, Ras or MEK/ERK1/2 would significantly reduce PVN apoptosis as indicated by changes of apoptosis-related proteins (p<0.05). AT1R inhibition would cause reduction in Ras-GTP and p-ERK1/2, but not vice versa; such intervention with corresponding inhibitors also suggested the unidirectional regulation of Ras to ERK1/2. Conclusion. These findings demonstrated that the activation of renin-angiotensin system in PVN could induce apoptosis through Ras/ERK1/2 pathway, which then led to increased sympathetic nerve activity and renal hypertension in 5/6Nx rats.